Determining exhaust fumes exposure in chainsaw operations. (November 2016) - Neri, F.; Foderi, C.; Laschi, A.; Fabiano, F.; Cambi, M.; Sciarra, G.; Aprea, M.C.; Cenni, A.; Marchi, E.
Abstract: The objective of this study was to investigate the inhalation exposure of forest operators to polycyclic aromatic hydrocarbons (PAHs) and BTEX (benzene, toluene, ethylbenzene and total xylenes) contained in the exhaust fumes released from chainsaws and to suggest possible countermeasures. The study was carried out in four silvicultural treatments (coppice clearcut, conifer thinning, conifer pruning, and sanitary cut), using three types of chainsaw fuel (normal two-stroke petrol mix and two alkylate fuels). Eighty personal air samples were collected; IOM samplers combined with Amberlite XAD-2 sorbent tubes were used for collecting PAHs and Radiello ® samplers were used for BTEX. Results indicate that none of the four silvicultural treatments significantly affected the PAHs and BTEX inhalation exposure of forest workers. On the other hand, statistically significant differences were recorded in the inhalation exposure to PAHs and BTEX when using different fuel types. In particular, the inhalation exposure to PAHs and BTEX was generally one order of magnitude lower when using modern alkylate fuels as compared to the traditional oil and lead-free petrol mixture. The small, non-statistically significant differences in inhalation exposure recorded between the two alkylate fuels suggests that the two fuels might be equivalent in terms of quality. Our study indicates that while forest workers are exposed to PAHs and BTEX, the maximum values are generally well below accepted occupational exposure limits. Graphical abstract: Highlights: Assessment of inhalation exposure of forest operators to exhaust fumes of chainsaw. Normal two-stroke petrol-oil mix and two alkylate fuels were compared. Inhalation exposure to BTEX and PAHs were lower than OEL. Different silvicultural treatments did not affect inhalation exposure values. Inhalation exposure to BTEX and PAHs was lower when alkylate fuels were used. Abstract : The value of inhalable PAHs and BTEX from chainsaw exhaust fumes is generally one order of magnitude lower from alkylate fuels than from the normal two-stroke mix.